Pengendalian Gerbang Otomatis Berjadwal Dengan Iot Dan Android - Romdoni, Mochammad Rizki; Safitri, Liza; Huda, Dwi Nurul; Mubarok, Sahrul; Supriyadi, N. (LPPM Universitas Putera Batam, 2024)
The development of information technology, especially the internet, has had a significant impact on various aspects of life. This research aims to utilize internet technology to automate the gate opening system. Specifically, this research will build a prototype of an automatic gate that can be controlled remotely through an Android application. This application allows users to set the gate opening schedule, monitor the gate status (open or closed), and receive notifications related to gate activity. As well as designing a prototype of a controller in the form of an application that can be installed on Android that can give commands to open the door with a button and schedule as well as notifications if the door is open and closed. The test results that the schedule gate application can be used to open the gate remotely and also the designed application can provide notifications and can control the gate to close and open